Adsorption of Congo Red from Aqueous Solutions by Alginate-Nanocellulose-Polyethyleneimine Hydrogel Beads - Amanda, Putri; Kurniawan, Yudhi Dwi; Prasetiyo, Kurnia Wiji; Hasan, Fahmi; Amelia, Anita (Trends in Sciences, 2023)
Biobased adsorbents have been developed for the removal of dye contaminants in aqueous solution. Hydrogel beads from alginate containing TEMPO-oxidized cellulose nanofibers (TOCNF) grafted with polyethyleneimine (PEI), namely Al/TOCNF-PEI, were prepared and evaluated as a new adsorbent for Congo Red (CR). The Al/TOCNF-PEI hydrogel beads were made with various concentrations of TOCNF/PEI, the optimum concentration is 45 wt% or Al/TOCNF-PEI45. The hydrogel was characterized by using Fourier-Transform Infrared spectroscopy and Scanning Electron Microscopy. The adsorption performance of the Al/TOCNF-PEI hydrogel beads towards CR was investigated in terms of changing of TOCNF-PEI content, initial concentration, pH, contact time, and adsorbent dosage. The maximum capacity of the adsorbent for CR was found to be 9.437 mg/g at the optimal conditions (pH = 3; T = RT) with the removal efficiency reaching 95 %. This result was ascribed to occur due to the electrostatic attraction between the protonated hydroxyl group and ammonium moiety of the hydrogel beads and the anionic sulfonate group of the CR. Upon fitting the adsorption data, the adsorption mechanism was consistent with the Freundlich isotherm and pseudo-second-order kinetic models. Based on this finding, the low-cost Al/TOCNF-PEI45 hydrogel beads demonstrated a great potential for the removal of hazardous dyes in wastewater. HIGHLIGHTS Biocomposites bead of Alginate containing TEMPO-oxidized cellulose nano fibers (TOCNF) grafted with polyethyleneimine (PEI) is promising Biobased adsorbents for removal congo red in aqueous solution. The biocomposite shows strong adsorption due to the electrostatic attraction between the protonated hydroxyl group and ammonium moiety of the hydrogel beads and the anionic sulphonate group of the CR. The high removal percentage was achieved at low starting dye concentration and pH, and high adsorbent doses Freundlich’s isotherm suggests multilayer adsorption of Congo red onto biocomposite beads GRAPHICAL ABSTRACT